2019
DOI: 10.1002/ab.21873
|View full text |Cite
|
Sign up to set email alerts
|

Investigating sexual harassment in online video games: How personality and context factors are related to toxic sexual behaviors against fellow players

Abstract: Online video games are social spaces for players from around the world. They use this space to form communities, relationships, and identities. However, gaming communities are not always welcoming, and some are even perceived as being "toxic." A prevalent issue is online sexual harassment, which is keeping many women from participating in the gaming community. Research on the factors contributing to the problem is limited, though. The present study replicates and expands previous research, using a sample of 85… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 66 publications
2
41
0
10
Order By: Relevance
“…This work builds on past research that has explored predictors of prejudice in online gaming (Fox & Tang, 2014; Hilvert‐Bruce & Neill, 2020; Tang & Fox, 2016; Tang et al, 2020) in several important ways. We present a more comprehensive model of predictors, including norms, individual differences, and gamer engagement, and are able to test the direct and indirect effects of personality and engagement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This work builds on past research that has explored predictors of prejudice in online gaming (Fox & Tang, 2014; Hilvert‐Bruce & Neill, 2020; Tang & Fox, 2016; Tang et al, 2020) in several important ways. We present a more comprehensive model of predictors, including norms, individual differences, and gamer engagement, and are able to test the direct and indirect effects of personality and engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research further extends our understanding of individual difference predictors of prejudiced behavior in online gaming by assessing a more comprehensive model of the predictors of sexism in online gaming (Tang, Reer, & Quandt, 2020). Hostile sexism, Social Dominance Orientation, sadism, narcissism, Machiavellianism, and gamer identification were tested as predictors of self‐reported sexual harassment in online video games.…”
Section: Introductionmentioning
confidence: 99%
“…Last but not least, we need to mobilize gamers themselves. Research has found that confronting toxic behaviors in games is one of the most effective ways to extinguish the behavior ( Whitty and Carr, 2006 ; Young and Jordan, 2013 ; Ridout and Campbell, 2014 ; Tang et al, 2020 ). However, recent reports indicate that only 18% ( Cary et al, 2020 ) to 20% of gamers say they stand up to harassment when they see it ( D’Anastasio, 2020 ), even though 76% of players ( Cary et al, 2020 ) felt prejudice should be confronted in online games.…”
Section: Moving Forwardmentioning
confidence: 99%
“…The interdisciplinary research project "Internet and Mental Health" (2016-2019) aimed to investigate the psychosocial effects of using online media. In Germany, a nationally representative survey of 1,929 adolescents and younger adults (aged 14-39 years) focused on topics such as social media and gaming disorder (Reer et al, 2020;Tang et al, 2020a), the fear of missing out (Reer et al, 2019), or sexual harassment in online contexts (Tang et al, 2020b). A primary goal of this project was to examine how the use of ICTs is associated with different indicators of mental health, loneliness, depression, and anxiety.…”
Section: Background and Literature Review Interdisciplinary Research mentioning
confidence: 99%